Influência de polimorfismos nos genes CYP2C9, VKORC1, MDR1 e APOE e variáveis sociodemográficas e clínicas na dose de varfarina em pacientes atendidos em três clínicas de anticoagulação em Belo Horizonte-MG - Emílio Itamar De Freitas Campos (2018)
Warfarin is the most widely used oral anticoagulant for treatment and prevention of thromboembolic disorders. Therapy monitoring is performed using International Normalized Ratio (INR), and time in therapeutic range (TTR) which is a measure of oral anticoagulation quality. In clinical practice, there is a wide variability in warfarin dose-response that is partially determined by genetic factors. There is evidence that genetic variations on CYP2C9, VKORC1, MDR1 and APOE genes may influence warfarin dose. This study aimed to evaluate sociodemographic, clinical factors and *1, *2 and *3 polymorphisms on CYP2C9 gene, -1639 G>A on VKORC1 gene, 3435 C>T on MDR1 and ε2, ε3 and ε4 on APOE influence at mean weekly warfarin maintenance dose. This is an observational cross-sectional study performed in three anticoagulation clinics in Belo Horizonte-MG. Patients were recruited between 2014-2015. Data were collected through patient interviews and medical chart review. Polymorphisms on CYP2C9, VKORC1, MDR1 and APOE were genotyped using Quantitative Polymerase Chain Reaction (qPCR). A gamma regression model was developed with variables significantly associated with warfarin dose. A calculated sample of 315 patients was included in the study. Mean age was 64.1±13.1 years, and 173 (54.9%) patients were female. The main indication for warfarin use was atrial fibrillation/flutter (n=240; 76.2%). Mean weekly warfarin maintenance dose was 28.5±13.1mg, and mean TTR was 65.5±17.9%. The regression model revealed that age, amiodarone use, genotype VKORC1 GA, genotype VKORC1 AA, genotypes CYP2C9*1/*2 or *1/*3 and genotypes CYP2C9*2/*2 or *2/*3 or *3/*3 were associated with warfarin dose reduction. These results suggest that sociodemographic, pharmacotherapeutic and genetic factors influence warfarin therapy. Together, this information allows us to get better knowledge of our population, and thus contribute to subsidize improvements in patient care process.